Multi - agent verification and validation for RFID system architecture - Muhammad Tarmizi Lockman, 1981-, author; Ali Selamat, author; International Conference on Electronic Desiign (2008 : Indonesia)i (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL